Evaluating microbiological quality of different kitchen equipment at different food premises - Salman, Hanis Syakira; Sazari, Lea Nursuria Sariza; P. Ramli, Rosnaini (2020)
Foodborne disease is the most serious public health problems that often threaten life. Foodborne disease is more common to high-risk groups including pregnant women, small children, older people, and those with poor immune systems. Foodborne illness or disease caused by the spoilage of infected food, viruses, food-contaminating parasites and most generally from pathogenic bacteria. Pathogenic bacteria such as E.coli, Salmonella and Staphylococcus aureus are the most prevalent. Pathogenic bacteria come from different sources such as consuming raw and uncooked eggs, undercooked poultry and meat, infected raw fruits and vegetables, raw milk, on healthy people and animals' skin, throat, and nostrils. As kitchen sponge becomes popular in every household for the cleaning of kitchen appliances, previous study has recorded that pathogenic bacteria grow on cooking appliances such as sponge, and utensils can be transferred into food. Our study is divided into three different types of food premises which are school canteen, restaurant and food court to target different ages and different groups. The study aims at measuring the growth of pathogenic bacteria in the kitchen sponge, identifying the presence of bacteria in the kitchen cutleries and measuring the efficacy of detergent use. The study found that school canteen recorded the highest growth of Salmonella (4 log10 cfu/ml), E.coli recorded the highest growth for restaurants (4 log10 CFU/ml), while food courts were contaminated with S.aureus (5.14 log10 CFU/ml). All food premises have recorded presence of pathogenic bacteria on kitchen cutleries except in R2 premise. The efficacy of the detergent also tested concludes that DSC1 is the most effective against selected bacteria in school canteen, DR1 in restaurant and DFC3 in food court. The findings in this study show that pathogenic growth of bacteria can offer a higher risk of developing foodborne disease to different ages.